Pengaruh Pembelajaran Kooperatif Model STAD dan Gaya Kognitif Terhadap Hasil Belajar Fisika Siswa SMA - Hendrik Arung Lamba (Universitas Negeri Malang, 2016)
This study was conducted to compare the achievement in physics between students taught using STAD-type cooperative learning and those taught conventionally, and between students having field-independent cognitive style and those having field-dependent using an experimental design, this study revealed that students taugh using STAD-type cooperative learning scored significantly higher in physics than those taught conventionally. In addition, students with field independent cognitive style were found to score significantly higher than the field dependent students. However, the study did not suggest any interactional effect of teaching model and cognitive style on student achievement.